2022
DOI: 10.4103/jfmpc.jfmpc_1189_21
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the pandemic: Analysis of demographic characteristics of COVID-19-infected patients during its two waves in Gwalior district of central India

Abstract: Background: Studies of pandemics in past centuries have suggested that the second wave was always more lethal and devastating as compared to the first wave. Regarding coronavirus disease (COVID) pandemic also, various speculations were made that during the second wave virus changes its nature either for age structure, gender or rural–urban differential. Present study was aimed to compare the demographic and mortality profile of COVID-19 patients during the two waves. Materials and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
(33 reference statements)
0
1
0
Order By: Relevance
“… 25 This finding contradicts the study reported in India. 29 Education status and marital status were significant with the COVID-19 infection in both waves.…”
Section: Discussionmentioning
confidence: 94%
“… 25 This finding contradicts the study reported in India. 29 Education status and marital status were significant with the COVID-19 infection in both waves.…”
Section: Discussionmentioning
confidence: 94%
“…Kelompok usia yang positif COVID-19 pada penelitian ini didominasi kelompok lansia (46-80 tahun). Hasil serupa juga dilaporakn oleh (17) yang menyebutkan bahwa pasien COVID-19 sebagain besar merupakan kelompok lansia. Lansia mempunyai risiko lebih tinggi terhadap angka kematian Hal ini disebabkan oleh beberapa faktor, antara lain penurunan sistem imun bawaan, penurunan sistem imun adaptif, perubahan epigenetik, dan peningkatan penyakit penyerta.…”
Section: Diskusi Karakteristik Demografi Sampelunclassified